STEELBAND WORKSHOP IN GERMANY (International Library of African Music, 1983)
A‘Steelband Non-stop Workshop’ was held in Wiesen, Austria, from 8 th May to 10th July 1983, organised by Dr Manfred Kremser, Inst für Völkerkunde der Universität Wien, A-1010 Vienna, Universitätsstr. 7, Austria.
Keywords: African Music